”Model native townships” in Suid-Afrika : “the pinnacle of perfection”? ʼn historiese evaluering, ca. 1900’s-1940’s - Harris, Karen Leigh (University of Pretoria, 2024)
Thesis (DPhil (History))--University of Pretoria, 2023.